Application of the Online-Based Titis Method in Learning Arabic Grammar from the SDGs Perspective - Wasilah; Jamanuddin; Alihan Satra; Ahmad Zaid Mabruk Ahmad; Muhammad Hafiz Alwan; Jumhur; Nazarmanto (Universitas Muhammadiyah Surakarta, 2025)
Objective: This study aims to analyze the implementation of the online-based Titis method in learning Arabic rules, especially nahwu, and shorof, at the Al Hafizh Indonesian Qur'an Language Institute. Theoretical framework: The theoretical framework underlying this study includes foreign language learning approaches as well as online learning theory, which emphasizes the importance of integrating teaching methods with digital media in increasing the effectiveness of the learning process. Literature review: The literature review in this study is likely to include studies on the Titis method, the teaching of nahwu and shorof, and the effectiveness of online Arabic learning through digital platforms such as Zoom, YouTube, and WhatsApp. Methods: This study uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation. Data analysis is carried out systematically through the stages of collection, presentation, verification, and conclusion, and uses triangulation to ensure the validity of the data. Results: The results of the study show that the Titis method is applied online through structured learning planning and implementation, including the use of digital media, learning modules, and periodic evaluations such as assignments, exercises, and final exams. Implications: This study shows that the Titis method can be effectively adapted into online learning and can be a reference for other Arabic language institutions in designing technology-based education programs. Novelty: The novelty of this study lies in the application of the Titis method online in the context of nahwu and shorof teaching, which has not been widely discussed in previous research, especially in a structured virtual learning environment.